Gestational diabetes mellitus and retinal microvasculature. Issue 1 (December 2017) - Li, Ling-Jun; Kramer, Michael; Tapp, Robyn; Man, Ryan; Lek, Ngee; Cai, Shirong; Yap, Fabian; Gluckman, Peter; Tan, Kok; Chong, Yap; Koh, Jia; Saw, Seang; et al.
Abstract Background Small-vessel dysfunction may be an important consequence of chronic hyperglycemia. We examined the association between gestational diabetes mellitus (GDM), a state of transient hyperglycemia during pregnancy, and retinal microvascular changes in pregnant women at 26–28 weeks of pregnancy. Methods A total of 1136 pregnant women with singleton pregnancies were recruited during their first trimester at two major Singapore maternity hospitals in an on-going birth cohort study. Participants underwent an oral glucose tolerance test and retinal imaging at 26–28 weeks gestation (n  = 542). We used the 1999 World Health Organization (WHO) criteria to define GDM: ≥7.0 mmol/L for fasting glucose and/or ≥7.8 mmol/L for 2-h post-glucose. Retinal microvasculature was measured using computer software (Singapore I Vessel Analyzer, SIVA version 3.0, Singapore Eye Research Institute, Singapore) from the retinal photographs. Results In a multiple linear regression model adjusting for age, ethnicity and maternal education, mothers with GDM had narrower arteriolar caliber (−1.6 μm; 95% Confidence Interval [CI]: −3.1 μm, −0.2 μm), reduced arteriolar fractal dimension (−0.01 Df; 95% CI: −0.02 Df, −0.001 Df;), and larger arteriolar branching angle (1.8°; 95% CI: 0.3°, 3.3°) than mothers without GDM. After further adjusting for traditional risks of GDM, arteriolar branching angle remained significantly larger in mothers with GDM than those without GDM (2.0°; 95% CI: 0.5°, 3.6°). Conclusions GDM was associated with a series of retinal arteriolar abnormalities, including narrower caliber, reduced fractal dimension and larger branching angle, suggesting that transient hyperglycemia during pregnancy may cause small-vessel dysfunction.